Long-term outcomes and clinical safety of expanded indication early gastric cancer treated with endoscopic submucosal dissection versus surgical resection: a meta-analysis - Na Gao; Xing Xu; Guoliang Zheng; Zhichao Zheng (BMJ Open)
Background and aims Endoscopic submucosal dissection (ESD) remains an investigational issue for early gastric cancer (EGC) with expanded indications owing to the risk of lymph node metastasis. In this study, we aimed to evaluate the clinical outcomes and safety of ESD versus surgical resection (SR) for EGC with expanded indications.Methods The systematic review selected studies from PubMed, Embase, Cochrane and Web of Science databases from 2010 to 2020, and compared survival and clinical safety data of ESD with those of surgical resection for EGC with expanded indications. The fixed-effects or random-effects model was used to calculate the differences between the two groups. To assess the validity of the eligible studies, risk of bias was measured using the Newcastle–Ottawa Quality Assessment Scale.Results Nine retrospective studies were used to calculate the differences in survival and clinical safety data between the two groups for EGC with expanded indications. Differences were not significant between the groups in terms of age, sex, tumour size, tumour histology or lesion morphology. Regarding tumour site, tumours located in the L area (the lower third of the stomach) were more likely to be found in the ESD group. With regard to metachronous and synchronous carcinomas, there was a significant difference favouring SR treatment (metachronous: OR=0.12, 95% CI=0.05 to 0.25, p<0.00001; synchronous: OR=0.11, 95% CI=0.02 to 0.46, p=0.003). Adverse event data were identified in six studies showing a significant difference favouring ESD treatment (ESD vs SR, OR=0.49, 95% CI=0.34 to 0.72. p=0.002). Additionally, six studies evaluating 5-year overall survival showed no significant differences between the two groups (HR=1.22, 95% CI=0.66 to 2.25, p=0.53). With regard to 5-year disease-free survival, patients with expanded indication EGC undergoing SR showed better survival (ESD vs SR, HR=3.29, 95% CI=1.60 to 6.76, p=0.001).Conclusion ESD provided favourable results for patients with EGC with expanded indications regarding clinical outcomes and safety in retrospective studies. Further, to detect synchronous or metachronous lesions, endoscopic surveillance should be performed following ESD. However, the included studies were observational, some did not have adequate adjustment for confounding factors and their results lacked generalisability due to their origin. Thus, further related randomised controlled trials are urgently encouraged.PROSPERO registration number CRD42021251068.